13. KEBIJAKAN KEAMANAN JEPANG TERHADAP PROLIFERASI NUKLIR KOREA UTARA PASCA KELUARNYA KOREA UTARA DARI REZIM NON-PROLIFERASI NUKLIR (PERIODE 2003-211) - Renni Novia Saputri Gumay; Tri Cahyo Utomo; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
North Korea’s nuclear proliferation has implicated threat toward Japan’s security directly,proven by illicit networks existence that support the nuclear proliferation program withinthe jurisdiction of Japan and indirectly, the capability of North Korea’s nuclear power to atany time could threaten the safety of Japanese citizens and Japanese territory. Threatescalation due to the North Korea’s nuclear proliferation is North Korea dared to conduct anuclear test in 2006 and 2009 after declaring withdrawal from regime of the Treaty on theNon-Proliferation of Nuclear Weapons (NPT). This nuclear issue has become internationalconcern, especially Japan. This research has purpose to analyze Japan’s security policybased on Japan’s identity as “pacifist country” and “non-nuclear country”. The frameworkused in this research is the concept of norms and identity of the constructivist theory. Thetype of this research is explanatory, using qualitative data analysis techniques fromliteratures review. The result of this research is given explanation about Japan’s securitypolicies which are normalization talk, international cooperation through ProliferationSecurity Initiative and Six Party Talk, and enhance its role as “stabilizer” in Asia region ininternational non-proliferation effort through Proliferation Security Initiative MaritimeInterdiction Exercise and Asia Senior-Level Talks on Non-Proliferation.